Community-Based Antiretroviral Therapy (ART) Delivery for Female Sex Workers in Tanzania: 6-Month ART Initiation and Adherence. - Tun, W.; Apicella, L.; Casalini, C.; Bikaru, D.; Mbita, G.; Jeremiah, K.; Makyao, N.; Koppenhaver, T.; Mlanga, E.; Vu, L. (AIDS & Behavior)
We conducted an implementation science study of a community-based ART distribution program for HIV-positive female sex workers (FSW) whereby clients received ART services through community-based mobile and home-based platforms. We compared 6-month treatment-related outcomes in the community-based ART arm (N = 256) to the standard facility-based ART delivery arm (N = 253). Those in the intervention arm were more likely to have initiated ART (100.0% vs. 71.5%; p = 0.04), be currently taking ART at the 6-month visit (100.0% vs. 95.0%; p < 0.01), and less likely to have stopped taking ART for more than 30 days continuously (0.9% vs. 5.7%; p = 0.008) or feel high levels of internalized stigma (26.6% vs. 39.9%; p = 0.001). In the adjusted regression model, internalized stigma (adjusted OR [aOR]: 0.5; 95% CI 0.28–0.83) and receiving community-based ART (aOR: 208.6; 95% CI 12.5–3479.0) were significantly associated with ART initiation. Community-based ART distribution model can improve linkage to and adherence to ART over standard facility-based ART programs for FSWs.